Mucormycosis - A Case Report Of A Disease Of An Environmental Concern (International Journal of Environmental Sciences, 2025)
Mucormycosis is a rare menacing fungal infection which affects the maxillary jaw more often. A potentially fatal invasive fungal infection, mucormycosis also known as zygomycosis or phycomycosis affects individuals who are immunocompromised such as poorly managed diabetes, hematological malignancies such as lymphoma, blood cancer, and organ transplant patients are traditional risk factors for mucormycosis. It is an angioinvasise disease caused by saprophytic fungi. Mucormycosis has a pronounced propensity to penetrate blood vessels, which can lead to thrombosis, necrosis, and tissue infarction.